Strategic Educational Management in Rural Public Schools: Driving Institutional Quality and Local Competitiveness - Moh. Gufron; Hikmah Eva Trisnantari; Junaidi Junaidi; Galuh Ajeng Nurazizah (LP. Ma'arif Janggan Magetan, 2026)
This study examines the contribution of the principal’s strategic management to improving educational quality and school competitiveness at SD Negeri 1 Wajak Lor. Using a descriptive qualitative approach, data were collected through semi-structured interviews, observations, and documentation, with the principal serving as the main informant. The findings indicate that effective strategic management is reflected in several key practices: (1) establishing a clear and measurable school vision as the basis for decision-making; (2) enhancing teacher competencies through continuous training and supervision to improve learning quality; (3) cultivating a positive school culture that encourages stakeholder engagement; (4) optimizing facilities and infrastructure to support teaching and learning activities; (5) strengthening partnerships with parents and external stakeholders to expand resource support; and (6) applying transformational leadership to address budget limitations and bureaucratic challenges. These strategies have contributed to increased student achievement, stronger community participation, and an improved school reputation. The study concludes that the principal’s strategic management plays a crucial role in advancing educational quality and institutional competitiveness. Consistent implementation of strategic planning, execution, and evaluation leads to better educational services and sustainable school development. Therefore, strengthening principal mentoring programs and practical managerial competencies is essential for supporting continuous improvement and long-term transformation in elementary education.